Change leadership and change embeddedness in public organizations: Connecting macrolevel reform to microlevel implementation - Higgs, Malcolm J.; Kuipers, Ben S.; Steijn, Bram (Public administration (London), 2023)
Governments initiate major public sector reforms for various reasons. Although change leadership appears crucial, its role in implementing reforms in public organizations receives scant attention. Insights from public administration and change management literature help to bridge the gap between these macrolevel and microlevel perspectives. Our multilevel study of two youth care organizations addressing public sector reform explores how leadership behavior—and in interaction between top and middle managers—contributes to the concept of what we call change embeddedness among front‐line employees. The use of leadership behaviors during the reform that are leader centric (shaping) appear to be associated with greater ambiguity and worse change embeddedness. However, leadership focused on engaging employees and boundary spanning with external organizations seems to support the embeddedness of the reform, especially when these behaviors are connected to a clear sense of purpose around the change.